THE IMPACT ANALYSIS OF AIMP2 MINILYRICS TOWARDS VOCATIONAL HIGH SCHOOL STUDENTS’ VOCABULARY MASTERY - Trinawati, Ratna; Anwar, Choiril (SIMPLE: International Journal of English Education, 2024)
This study was about the use of Aimp2 MiniLyrics as teaching learning media to improve students’ vocabulary mastery. In order to achieve the study, the writer used quasi-experimental research design. The population of this study was the eleventh-grade students of vocational high school and the samples of the study was class XI TEI.1 (Teknik Eleektronika Industri) consist of 38 students who formed the control group and class XI TP.1(Teknik Pemesinan) consist of 37 students who served as the experimental group. In collecting the data, the writer used vocabulary test to measure the students’ vocabulary mastery and it was administered twice, namely pre-test and post-test. The data then, was analyzed by using SPSS for windows release version 16.0. Based on statistics analysis, it can be seen that t-test was higher than t-table (3,9411,993) and sig (2-tailed) was 0.000 0.05. It means that there was a development in students’ vocabulary mastery after getting the treatment. From the result, it can be concluded that Aimp2 MiniLyrics as material can be used to improve students’ vocabulary mastery.